Corporation for Public Broadcasting Mission and Goals, Tasks and Responsibilities. - Corporation for Public Broadcasting, Washington, DC.; Corporation for Public Broadcasting, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This brochure contains two statements adopted by the Corporation for Public Broadcasting (CPB), one outlining the Corporation's mission and goals, and the other outlining its tasks and responsibilities. The mission of the CPB is to take the lead in developing a uniquely American non-commercial public radio and television system that will inform, enlighten and enrich the lives of the people. Its goals, from which its tasks and responsibilities are derived, include supporting local stations, raising the quality of programing, developing unexplored potential, guiding the development of interconnection systems for public radio and television stations, ascertaining audience needs, publicizing Public Broadcasting, and guarding its freedom. (WBC)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Broadcast Industry; Objectives; Policy; Programing (Broadcast); Public Television; Corporation for Public Broadcasting; Guides, General